Kewenangan dan Efektivitas Pengawasan Badan Permusyawaratan Desa terhadap Penyelenggaraan Pemerintahan Desa - Ismawardi Ismawardi; Syariffuddin Syariffuddin; Bambang Sasmita Adi Putra (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The Village Consultative Body (BPD) is constitutionally recognized under Article 18B(2) of the 1945 Constitution and strengthened by Law Number 6 of 2014 concerning Villages, which establishes the BPD as an equal partner to the village head in ensuring checks and balances. However, its legal authority is often not reflected in practice, particularly in Teluk Sungka Village, Indragiri Hilir Regency. This study examines the implementation of the BPD’s supervisory function and the factors affecting its effectiveness using a juridical-normative method with statutory and conceptual approaches. The findings show that BPD supervision covers village regulations, financial management, and the village head’s performance, but remains largely administrative due to limited human resource capacity, kinship-based relationships, and weak community participation. The study concludes that effective BPD supervision requires stronger institutional capacity, regulatory certainty, and greater public legal awareness to promote transparent and accountable village governance.